Quality Control Analysis on Animal Feed Storage to Minimize Defect Using Six Sigma Method in PT XYZ - Asmaul Husna; Dira Ernawati (Yayasan Kita Menulis, 2025)
As the industrial world develops, companies are required to produce quality products to attract consumer interest in order to survive in the midst of intense competition in the industrial world, including companies in the animal feed industry. Therefore, quality control is an activity that must be carried out so that the products produced have good quality. At PT XYZ, there are defects in animal feed storage such as expired, ticky, tilted plots, and leaky sacks. To handle these problems, an analysis is carried out using the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, and Control) stages. Based on company data from January to October 2024, the defects amounted to 1.459 sacks with the most types of defects in the form of leaky sacks with a percentage of 83%. The DPMO value obtained shows that there is a possibility of 59.726 defects for a million production with a sigma level value of 3,125. This value shows that the quality is still not consistent and maximum, so improvements need to be made to improve quality and sigma level. Thus it is expected that the company can become a competitive company and can compete well in the industrial world.